Paciente de sexo femenino de 50 años de edad con neominia asociada a la ventilación mecánica. - Carriel Montenegro, Keyla Denise (2020)
The present clinical case deals with a 50-year-old female patient diagnosed with HIV and Pneumonia associated with mechanical ventilation, a complication that occurred after the patient was admitted to the intensive care unit. Pneumonia associated with mechanical ventilation is one of the first causes of mortality in patients who are under mechanical ventilation, be it due to tracheostomy or endotracheal tube, this complication occurs because there is no voluntary elimination of secretions accumulated in the airway. Through this study we are going to know the risk factors that will lead to pneumonia associated with mechanical ventilation, and in turn we will know the measures that must be taken to avoid this type of complication.